Chinese Public Intellectuals’ Call for Constitutionalism. Yu Jianrong’s and Xu Zhiyong’s Advocacy and Engagement - Yoochadchawan, Tais (fi=Turun yliopisto|en=University of Turku|, 2017)
In 2012 China celebrated 30th anniversary of its Constitution, with the General Secretary of the CCP Xi Jinping presenting a speech and stressing the supreme status of the fundamental law. The speech was in accordance with the state policies that prevailed in pervious years: promotion of “people-oriented governance” and implementation of the rule of law. Such policies, together with a relaxed ideological environment and the growth of increasingly pluralistic citizenry with greater consciousness of its rights facilitated freer debates of pubic intellectuals’ on political reforms and constitutionalism. Moreover, some public intellectuals have stepped out from the traditional capacity of experts or intellectuals and become engaged in civic activism. The presented study seeks to “start filling” the gap in existing scholarly works on the individual public intellectuals who are involved in advocacy and activism in China and introduce them to broader public. Particularly, it focuses on two prominent Chinese intellectuals - Yu Jianrong and Xu Zhiyong - who have advocated through their works and activism for constitutionalism and the rule of law. The thesis focuses mainly on years of their engagement during the Hu-Wen era, since Xu Zhiyong was arrested in the late 2013, the first full year of Xi Jinping era. This thesis attempts to provide in-depth examination and analysis of Yu Jianrong’s and Xu Zhiyong’s motives, actions and activities. It seeks to explore why these individuals decided to raise their voices for constitutionalism and get involved in activism and advocacy; how they advocated for their goals and how they interacted with the authorities. The first chapter provides an overview of the purpose and methodology of the research, focusing on the sources. Furthermore, it explicates major concepts used in the study. The second chapter follows Yu Jianrong’s and Xu Zhiyong’s childhood and youth experiences and possible explains motives of their civic engagement and advocacy. The third chapter draws on main topic of Yu’s and Xu’s interests and their activism works through which they execute their advocacy for constitutionalism and rights. The fourth part addresses their relationships with the Party-state, demonstrating how they operated under changing state discourses and the diminishing tolerance for civil society. By presenting stories of engagement and advocacy of Yu Jianrong and Xu Zhiyong, I sought to demonstrate that dominating in the West perception of black-white relations between the state and opposition misses nuances and overshadows Chinese intellectuals who by manoeuvring the system rather than fighting it attempt to push for political reforms and constitutionalism.